Answer:
4Hz
Step-by-step explanation:
Standard form of a sine or cosine function,
y = acos(b(x+c))
where a is the amplitude, b is the value to find the period. and c is the phase shift.
Period = \frac{2\pi}{b}
From the equation given in the question,
![y = 3cos(8\pi \: t + \frac{\pi}{2} ) \\ y = 3cos(8\pi(t + \frac{1}{16} )) \: \: (factorising \: 8\pi \: out)](https://tex.z-dn.net/?f=y%20%3D%203cos%288%5Cpi%20%5C%3A%20t%20%2B%20%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%29%20%5C%5C%20y%20%3D%203cos%288%5Cpi%28t%20%2B%20%20%5Cfrac%7B1%7D%7B16%7D%20%29%29%20%5C%3A%20%20%5C%3A%20%28factorising%20%5C%3A%208%5Cpi%20%5C%3A%20out%29)
We can see:
Amplitude = 3,
Period = \frac{2\pi}{8\pi} = 1 / 4
Phase Shift = 1 / 16
Now we want to find the frequency.
Frequency = 1 / Period
= 1 / (1/4)
= 4Hz
<u>Answer:</u>
If f(x) = -3x - 5 and g(x) = 4x - 2 then (f - g)(x) = -7x - 3
<u>Solution:</u>
We need to determine the value of (f - g)(x)
Given that the function is f(x) = -3x - 5 and the other function is g(x) = 4x - 2
The value of (f - g)(x) can be found by as follows:
<em>(f - g)(x) = f(x) - g(x)</em>
On substituting the given value of f(x) and g(x) we get
(f - g)(x) = (-3x - 5) - (4x - 2)
Upon solving we get
(f - g)(x) = -3x -5 -4x + 2 = -7x -3
Hence the value of (f - g)(x) is equal to -7x - 3
The answer is c ................
Answer:
I think it is triangular prisim
Angle A = angle U since they're both right angles (both 90 degrees). This is what the square marker means.
segment AC = segment UW
Angle C = angle W because they have the same angle marker
---------------------
we have two pairs of congruent angles, with segments between them that are congruent. So we use the ASA property
The final answer is choice E.